2018
DOI: 10.5354/0719-0581.2018.50742
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: b Universidade do Vale do Rio dos Sinos, Rio Grande do Sul, BrasilO presente estudo objetivou identificar a prevalência e os preditores da adição ao trabalho em uma amostra de 392 gestores Brasileiros. Como instrumentos de pesquisa, foram utilizados um questionário sociodemográfico e laboral, a Dutch Work a Addiction Scale, a Utrecht Work Engagement Scale, a Escala de Satisfação com a Vida e a Escala de Foco Regulatório. A análise dos dados foi realizada por meio de regressão linear múltipla para as duas dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…People addicted to work performs activities far beyond the proposals, not doing them because they are asked, but because they believe they are necessary and ends up getting in the way of their daily routines due to the high expectations on themselves, showing a lack of control over the hours dedicated to work and about the work itself (5) , which can harm their quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…People addicted to work performs activities far beyond the proposals, not doing them because they are asked, but because they believe they are necessary and ends up getting in the way of their daily routines due to the high expectations on themselves, showing a lack of control over the hours dedicated to work and about the work itself (5) , which can harm their quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported workaholism as one of the causes of workers' mental and physical illness (1)(2)(3) . It is estimated that 10% of North Americans are workaholic (4) , this condition being more prevalent among workers who perform activities at the managerial level and specific sectors, such as health professionals and teachers (5) .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the above, few studies have identified the prevalence and factors associated with workaholism among individuals inserted in the work process of the different fields of activity in the public or private sector (1)(2)(3) , especially among nursing professors from PPGEnf. Studies that fill this gap are essential to support management actions and public policies about the risks to workers' health since workaholism is a pathological condition that implies a decrease in professional performance, presenteeism (12) , techno-stress (7) , burnout (13) , deterioration of interpersonal relationships, mainly social and family relationships (2) , increased cardiovascular risk (14) and karoshi, the sudden death from overwork (15) .…”
Section: Introductionmentioning
confidence: 99%
“…In another study with a Brazilian sample of 392 managers, the results showed that workaholism predicted satisfaction with life and that workaholism was a psychological phenomenon that affected the health and well -being of managers and bosses (Pinheiro & Carlotto, 2018). Liang and Chu (2009) studied the personality traits that cause workaholism in a sample of Chinese employees.…”
mentioning
confidence: 99%